2011
DOI: 10.1371/journal.pone.0025421
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Resveratrol against Botrytis cinerea Is Improved Using 2-Furyl Derivatives

Abstract: The antifungal effect of three furyl compounds closely related to resveratrol, (E)-3,4,5-trimethoxy-β-(2-furyl)-styrene (1), (E)-4-methoxy-β-(2-furyl)-styrene (2) and (E)-3,5-dimethoxy-β-(2-furyl)-styrene (3) against Botrytis cinerea was analyzed. The inhibitory effect, at 100 µg ml−1 of compounds 1, 2, 3 and resveratrol on conidia germination, was determined to be about 70%, while at the same concentration pterostilbene (a dimethoxyl derivative of resveratrol) produced complete inhibition. The title compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 50 publications
2
50
0
3
Order By: Relevance
“…The first one is the direct action of the antibiotic compound on the pathogen (Caruso et al 2011). It seems, however, that this mechanism does not apply in our experiment.…”
Section: General Overview On Possible Directions Of Resveratrol Actiomentioning
confidence: 63%
“…The first one is the direct action of the antibiotic compound on the pathogen (Caruso et al 2011). It seems, however, that this mechanism does not apply in our experiment.…”
Section: General Overview On Possible Directions Of Resveratrol Actiomentioning
confidence: 63%
“…UV-C treatments have been successfully used to increase the content of bioactive compounds with beneficial effects for the consumer in fruits, such as grapes (Cantos et al, 2001). Such increase might also favor fruit resistance to fungal development, as resveratrol and its derivatives are phytoalexins with strong antifungal activity (Caruso et al, 2011). In the preliminary study, regarding the effect of the different treatments on the sensory quality of grapes from these preliminary tests, it was observed that a UV-C light treatment at 6 kJ/m 2 did not cause any detrimental effect either on the visual quality or in the flavor as no significant difference was observed between untreated and treated grapes for these quality parameters ( Fig.…”
Section: Selection Of Postharvest Treatmentsmentioning
confidence: 99%
“…Por otra parte, el crecimiento micelial de B. cinerea in vitro se inhibió entre 50 y 70 % por acción de RVS (Salgado et al, 2015). Además, al evaluar la efectividad, de manera separada, de RVS y tres compuestos relacionados con éste, (E)-3,4,5-trimethoxy-β-(2-furyl)-estireno, (E)-4-methoxy-β-(2-furyl)-estireno y (E)-3,5-dimethoxy-β-(2-furyl)-estireno a 100 µg/mL, se logró inhibir 70 % de la germinación de conidios de B. cinerea (Caruso et al, 2011).…”
Section: Fully Bilingualunclassified
“…On the other hand, micelial growth of B. cinerea in vitro was inhibited between 50 and 70 % by the action of RVS (Salgado et al, 2015). Also, when individually assessing the effectiveness of RVS and three RVS-related compounds, (E)-3,4,5-trimethoxy-β-(2-furyl)-styrene, (E)-4-methoxy-β-(2-furyl)-styrene and (E)-3,5-dimethoxy-β-(2-furyl)-styrene at 100 µg/mL, 70 % of B. cinerea conidia germination was inhibited (Caruso et al, 2011).…”
Section: Fully Bilingualmentioning
confidence: 99%